The Customer-Centric Approach: Evaluating Family Takaful Products at Fwd Takaful Berhad - Ismail, Sukriah; Abu Bakar, Marina; Hussain, Hanizan Shaker; Anuar, Mohamad Saufee; Ali, Md Nasri (Journal of Entrepreneurship, Business and Economics; Vol 13 No 1 (2025), 2025)
This study aims to evaluate the management efficiency of family takaful products at FWD Takaful Berhad, focusing on customer preferences and the factors influencing them; specifically religious, ethical and practical considerations. Utilizing quantitative methods, the study employs regression analysis to examine the relationships between customer preferences and these influencing factors, with data collected through a structured survey and analyzed using AMOS software to identify key trends and correlations. The findings reveal significant relationships between customer preferences and religious compliance, ethical conduct of takaful operators, and practical usability, suggesting that customer preferences are strongly influenced by these factors and highlighting the need for alignment between family takaful products and customer values. While the study is limited to FWD Takaful Berhad and may not be generalizable to other operators, the insights gained offer a valuable understanding of customer behaviors in the Islamic financial sector. This study provides critical insights for takaful operators, emphasizing the importance of incorporating religious, ethical, and practical factors into product development and marketing strategies to improve customer satisfaction and loyalty. It contributes to the growing body of research on customer preferences in the takaful industry, providing actionable recommendations for enhancing product offerings and aligning them with customer expectations. Research Paper Keywords: Family Takaful, Customer Preferences, Management Efficiency, Islamic Finance, FWD Takaful Berhad Reference to this paper should be made as follows: Ismail, S., Abu Bakar, M., Hussain, H.S., Anuar, M.S., & Ali, M.N. (2025). The Customer-Centric Approach: Evaluating Family Takaful Products at Fwd Takaful Berhad. Journal of Entrepreneurship, Business and Economics , 13 (1), 55–101.